Tensiones en el desarrollo cognitivo en los niños y niñas de 5 a 6 años del primer año de educación básica, del sector rural del cantón Latacunga parroquia Guaytacama - Cárdenas Chiguano, Jennifer Alexandra (2017)
The present research Project has as a purpose to make the study of the educative problems and diagnose compile, identify and analyze the tensions in the cognitive development in children from 5 to 6 years old of the first year of basic education, located in Latacunga city in parish called Guaytacama, it is essential to determine the work environment with the purpose of attend the attend the general necessities in the teaching learning process. Therefore, are an important part parents and members of the educational community, for this way enrich the infant knowledge and to be alert of the emotional state and the personal characteristics of them establishing standards of coexistence inside and outside to the education environment assuring that the child feel safe increasing their confidence and seld-esteem. The focus of this research is qualitative – quantitative, It is qualitative because is normative explicit realist an quantitative, because was made with statical data which permit as deduce the obtained date to know the level of tension in the learning of them. In the institution, the observed tensions in the classroom of the first year of basic education throung of the list comparison....